Polyadenylation of mRNA: minimal substrates and a requirement for the 2' hydroxyl of the U in AAUAAA. - Wigley, P L (1990)
mRNA-specific polyadenylation can be assayed in vitro by using synthetic RNAs that end at or near the natural cleavage site. This reaction requires the highly conserved sequence AAUAAA. At least two distinct nuclear components, an AAUAAA specificity factor and poly(A) polymerase, are required to catalyze the reaction. In this study, we identified structural features of the RNA substrate that are critical for mRNA-specific polyadenylation. We found that a substrate that contained only 11 nucleotides, of which the first six were AAUAAA, underwent AAUAAA-specific polyadenylation. This is the shortest substrate we have used that supports polyadenylation: removal of a single nucleotide from either end of this RNA abolished the reaction. Although AAUAAA appeared to be the only strict sequence requirement for polyadenylation, the number of nucleotides between AAUAAA and the 3' end was critical. Substrates with seven or fewer nucleotides beyond AAUAAA received poly(A) with decreased efficiency yet still bound efficiently to specificity factor. We infer that on these shortened substrates, poly(A) polymerase cannot simultaneously contact the specificity factor bound to AAUAAA and the 3' end of the RNA. By incorporating 2'-deoxyuridine into the U of AAUAAA, we demonstrated that the 2' hydroxyl of the U in AAUAAA was required for the binding of specificity factor to the substrate and hence for poly(A) addition. This finding may indicate that at least one of the factors involved in the interaction with AAUAAA is a protein.